KAJIAN KUALITAS AIR SUMUR SEBAGAI SUMBER AIR MINUM DI KELURAHAN GUBUG KECAMATAN GUBUG KABUPATEN GROBOGAN - Aqnes Budiarti; Rupmini Rupmini; Henna Rya Soenoko (Universitas Wahid Hasyim Semarang, 2013)
ABSTRACT Most of Grobogan people use well water facilities to fulfill water requirement every day. This study aim to evaluate well water quality that used as water drinking resourses in Gubug Grobogan and to determine well water meet the requirement as Regulation of Health Minister No. 416/Menkes/Per/IX/1990. This study is non-experimental research with descriptive analysis. Parameter of water quality that investigated comprised physical parameter, chemical parameter and microbiological parameter. Sample have been taken by simple random sampling from three types of well in Gubug, that is well near the garbage disposal, well near the Gubug village river which all along the river there are tofu factory